Postoperative adrenal insufficiency in Conn's syndrome-does it occur frequently? - Zelinka, Tomáš; Petrák, Ondřej; Waldauf, Petr; Zítek, Matěj; Holaj, Robert; Forejtová, Lubomíra; Michalský, David; Novák, Květoslav; Dušková, Jaroslava; Springer, Drahomíra; Widimský, Jiří (Journal of human hypertension, 2022)
Primary aldosteronism (PA) is the most frequent form of endocrine hypertension. Recently, frequent clinically significant adrenal insufficiency after adrenalectomy in subjects with PA has been reported, which may make the early postsurgical management difficult. We retrospectively searched for possible adrenal insufficiency in subjects who underwent adrenalectomy for PA and have measured cortisol in the early postoperative course. We included subjects with confirmed diagnosis of PA who underwent either posture testing (blood draw at 06:00 and 08:00) and/or adrenal venous sampling (AVS) (blood draw between 08:00 and 09:00) and have also measured cortisol after surgery (cortisol measured approximately at 07:00). Cortisol was measured by immunoassay. In this study, we identified 150 subjects (age 48.5 ± 10.3 years) with available cortisol values in the early postoperative course (median [25th percentile, 75th percentile]) 6 [5,6] days. Postoperative cortisol values (551 ± 148 nmol/l) were normal and significantly higher, compared to preoperative standing cortisol values (404 ± 150 nmol/l; (P < 0.001) and AVS cortisol values (493 ± 198 nmol/l; P = 0.009), and did not significantly differ from preoperative supine cortisol values. Postsurgical cortisol values were not different among subjects with or without abnormal dexamethasone suppression test or elevated urinary free cortisol pre-surgery, and were significantly higher in subjects with abnormal diurnal cortisol variability compared with subjects with normal diurnal variability. No patient presented with adrenocortical crisis in the later follow-up. In conclusion, postoperative cortisol values did not indicate any suspicion of possible adrenal insufficiency. To exclude possible adrenal insufficiency, it may be sufficient to measure morning cortisol in the early postoperative course.
Keywords: adrenalektomie; dospělí; hydrokortison; Adrenalectomy; lidé středního věku; lidé; retrospektivní studie; Hydrocortisone; Hyperaldosteronism; adrenální insuficience; hyperaldosteronismus; Adrenal Insufficiency; Retrospective Studies; Middle Aged; Adult; Humans